A Second Review of the Dissocial Behavior Scale: The Graffiti Factor - Moral de la Rubia, José (Consorcio de Universidades Mexicanas A.C., 2012)
The aim of the present study was to conduct a second review of the 27-items Dissocial Behavior Scale (ECODI27-R, Moral & Pacheco, in press), generating and selecting new indicators for graffiti factor that showed internal consistency problems. Dissocial behavior was defined as a pattern of disruptive behavior in children and adolescents who persistently violate the basic rights of others through aggression, destruction of property, dishonesty, theft and serious violations of rules. The scale was administered to an incidental sample of 245 Baja California high school students (114 men and 131 women). We achieved to retain 27 items losing four (two of Robbery, one of Pranks and one of Disputes) and adding new four items for graffiti factor that reached high internal consistency. The scale also retained its six correlated factors with a proper fit to the data, all of them with high values of internal consistency; negative asymmetric distributions, except Pranks presented normal distribution. Men reported significantly more dissocial traits. Dissocial traits correlated with higher number of siblings and lower family income. Therefore the ECODI-27-R2 scale is a reliable and valid and improvements in compare to the previous two versions. It is suggested testing the scale at the high school level for setting its norms by means of percentiles using a probabilistic sample of students.